Psychometric Validation of the Persian Version of Multidimensional Health Locus of Control Scale (MHLC-C) for Menopausal Women - Khadijeh Khademi; Mohammad Hossein Kaveh; Mahin Nazari; Abdolrahim Asadollahi (Advances in Public Health)
Background. The Health Locus of Control (HLC) serves as a mediator between an individual’s behaviors and health status, influenced by various cultural, environmental, and situational factors. Its measurement reflects health beliefs and attitudes, ultimately leading to healthy behaviors. Menopause is a significant phenomenon in women’s lives, often resulting in a wide range of symptoms and health issues. Therefore, the perception of HLC plays a crucial role in promoting healthy behaviors and managing menopausal symptoms. This study aimed to assess the validity and reliability of the Persian version of the short form Multidimensional Health Locus of Control Scale (MHLC) in Iranian menopausal women and explore its interrelationships. Methods. A cross-sectional study was conducted with 271 menopausal women from September to November 2023. Psychometric properties such as construct validity (confirmed through confirmatory factor analysis), convergent validity (evaluated using average variance extracted), and internal consistency (assessed by Cronbach’s alpha, composite reliability and rho_A factor) were examined. Discriminant validity was determined using the Fornell–Larcker criterion. Reliability was further established through Cronbach’s alpha and McDonald’s Omega coefficients. The predictive relevance of the model and associations between constructs were analyzed using various statistical measures. Data analysis was conducted using SPSS v.27 and Smart PLS 3.0 software. Limitations of this study include that it was conducted in urban health centers, only women with at least primary education were included, and reliance on self-reported data. Results. The initial stage of construct validity involved the Kolmogorov–Smirnov test, with confirmatory factor analysis demonstrating a good model fit. Significant correlations were found between internal health control and factors related to doctors and other people, indicating that internal health control directly influences these factors in managing menopausal symptoms and health problems. Cronbach’s alpha and McDonald’s Omega coefficients for the 13-item MHLC-C scale were satisfactory (0.81 and 0.72, respectively). Conclusions. The Persian version of the 13-item MHLC-C has been validated as a reliable tool for assessing the health locus of control in Iranian menopausal women. Internal health control was found to significantly impact perceptions related to doctors and other people, highlighting its importance in managing menopausal symptoms effectively.